Competitive development of the economy based on the system of labor force motivation indicators - Shmygol, Nadiia; Polcyn, Jan; Sobczak-Michałowska, Marzena; Andrii, Antoniuk (<center>Conference Proceedings Determinants Of Regional Development</center>, 2022)
One of the most pressing and urgent tasks of a modern leader is to stimulate labor activity, since it is labor resources that are the driving force of any economic processes. Such stimulation is possible by building an effective motivation system based on motivational factors. In turn, the motivation system should provide: - a way of attracting labor activity and retaining highly qualified personnel with the highest level of human capital; - the formation of a corporate culture, taking into account the social responsibility of business; - achievement of the strategic development goals of the organization on the basis of building a system of sustainable competitive advantages. The relevance of these issues is also confirmed by the need to ensure the growth of labor productivity caused by the rapid reduction in the number of labor resources in Ukraine, due to the demographic crisis of previous years. In view of the above, the purpose of this research is to study the competitive development of the economy based on a system of indicators of labor force motivation.